Generating the evidence for marine fisheries policy and management - Holmes, J; Lock, J (2010)
The uptake of research in marine fisheries management and policy making depends on how effectively fisheries managers, researchers and scientific advisers communicate the needs for evidence, and the results and policy implications of research. The MariFish network of the major European funders of marine fisheries has therefore undertaken a study of current practices relating to communication of research needs and results, identifying strengths and weaknesses, and consequently how two-way communications, and hence the effectiveness of generating evidence for marine fisheries policy making and management, can be improved. Conclusions and recommendations for 'good practice' include the importance of building good relationships and trust between researchers and fisheries managers, the need for fisheries ministries to have sufficient inhouse scientific capacity to act as 'intelligent customers', and the key role of interpreters of research whose skills and career paths need to be carefully developed. © 2009 Elsevier Ltd.